STRATEGI HILIRISASI PENDIDIKAN KARAKTER DALAM MEMBENTUK KEMANDIRIAN DAN KREATIVITAS PESERTA DIDIK SEKOLAH DASAR - Mutmain Tangkudung; Uznul Zakarina; Sulistyawati Katili; Acal Liputo (Tadbir: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to analyze the downstream strategy of character education in shaping the independence and creativity of students in elementary schools. The background of the research departs from the importance of character education which is not only taught theoretically, but also practiced in real activities so that students are able to internalize these values in daily life. The research method used is a qualitative approach with observation, interview, and documentation techniques to obtain in-depth data. The results of the study show that the downstream strategy is able to increase children's independence, characterized by the courage to make decisions, self-management, and responsibility for tasks. Students' creativity also develops through project-based activities, simulations, and contextual learning that provide space for experimentation and imagination. The role of teachers as facilitators has proven to be crucial in creating a learning environment that encourages freedom of expression, while parental support strengthens the application of character values at home.